1999
DOI: 10.1002/crq.3900160406
|View full text |Cite
|
Sign up to set email alerts
|

African Americans in mediation literature: A neglected population

Abstract: This article examines mediation literature for the presence of culturally specific literature on the African American population in the United States. A review of mediation literature has exposed a culturally specific literature‐based void that has not empirically investigated African Americans as the primary subject in terms of practice and research‐related aspects of the mediation process. This article explores how the neglect of this population in the literature has negative implications for practice and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Identity and cultural issues are always present in ombudsman interactions, although they may not be readily apparent. The serious lack of minority practitioners and perceptions of Eurocentric bias have long been sources of concern within the field of mediation, as have concerns about differences of class, language, and ethnic background (Hairston ). Therefore, our approach must be to understand the implications of these issues and to create strategies for addressing them.…”
Section: Strategies For Addressing Identity Issues Within Ombuds Relamentioning
confidence: 99%
“…Identity and cultural issues are always present in ombudsman interactions, although they may not be readily apparent. The serious lack of minority practitioners and perceptions of Eurocentric bias have long been sources of concern within the field of mediation, as have concerns about differences of class, language, and ethnic background (Hairston ). Therefore, our approach must be to understand the implications of these issues and to create strategies for addressing them.…”
Section: Strategies For Addressing Identity Issues Within Ombuds Relamentioning
confidence: 99%
“…provide the impetus for those intergroup interactions. Accordingly, Hairston (1999) argues that too little research on the conflict orientations of groups with nonmajority cultural experiences has led to a "culturally specific void" (p. 357) in the CR literature; thus, the knowledge and skills of CR practitioners as they relate to diverse perspectives are left wanting. The consequences of this void became apparent during the National Conference on Peacemaking and Conflict Resolution's (NCPCR) Cultural Bridges Coalition meeting when Native, African, Latin, and Asian American participants indicated that with regard to "cultural competence," mainstream conflict resolution processes mandated "vast adaptations" on their parts (Baker, French, Trujillo, and Wing, 2000).…”
mentioning
confidence: 99%
“…[Yet], there is much less research done and even published on the effect of conflict resolution education on diverse populations, let alone from the perspective of those from diverse populations" (Baker, French, Trujillo, and Wing, 2000, p. 64). Hairston (1999) proposes that the absence of culturally specific research and literature produces a "hegemonic control of knowledge" and "renders issues of concern to African Americans unimportant and unworthy of scholarly attention" (p. 362).…”
mentioning
confidence: 99%
See 1 more Smart Citation